2016
DOI: 10.1098/rsbl.2016.0059
|View full text |Cite
|
Sign up to set email alerts
|

Are invasive fire ants kept in check by native aerial insectivores?

Abstract: Aerial predator–prey interactions may impact populations of many terrestrial species. Here, we use altitude loggers to study aerial foraging in a native insectivore, the purple martin ( Progne subis ), in the southern USA. Purple martins fed primarily on mating queens and males of the invasive red imported fire ant ( Solenopsis invicta ), and doubled their foraging efficiency by doing so. Across the USA, purple martins likely eat billions of fire ant queens each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Among aerially mating ants, for example, body size accounted for nearly 90% of variation in flight altitude. Mirroring their dominance on land, winged sexuals of ants and other social insects also play a prominent role in aerial food webs as abundant and nutritious prey 30 . The role of flight in ant biology is often overlooked because most individual ants are wingless workers that live in earthbound colonies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among aerially mating ants, for example, body size accounted for nearly 90% of variation in flight altitude. Mirroring their dominance on land, winged sexuals of ants and other social insects also play a prominent role in aerial food webs as abundant and nutritious prey 30 . The role of flight in ant biology is often overlooked because most individual ants are wingless workers that live in earthbound colonies.…”
Section: Discussionmentioning
confidence: 99%
“…Ant sexuals are relatively defenseless, and the bodies of queens contain large reserves (up to 70% body weight) of fats, storage proteins, and glycogen that help them found new colonies 24 25 . Ant sexuals are therefore an abundant and nutritious target for predators 26 27 28 29 30 , and their mating swarms may provide substantial nutrient inputs into aerial food webs.…”
mentioning
confidence: 99%
“…In volant birds, flight performance contributes to many ecologically relevant functions, including mate displays (Clark, ; Clark & Feo, ; Usherwood, ), prey capture (Helms, Godfrey, Ames, & Bridge, ; Warrick, Hedrick, Biewener, Crandell, & Tobalske, ), predator escapes (Kullberg, Fransson, & Jakobsson, ; Kullberg, Jakobsson, & Fransson, ; van den Hout, Mathot, Maas, & Piersma, ), and arrival time to migration grounds (Bowlin & Winkler, ; Matyjasiak, ). Thus, flight performance can potentially affect both reproductive success (via mate choice; reviewed in Barske, Schlinger, Wikelski, & Fusani, ; Byers, Hebets, & Podos, ) and survival (Møller, ).…”
Section: Introductionmentioning
confidence: 99%
“…; Daly ; Wing ; Helms et al. ) could select for virginity as an alternative reproductive strategy for haplodiploid females (Godfray and Hardy ; Godfray and Cook ; Tilquin ).…”
mentioning
confidence: 99%
“…If selection would favor high frequency of virgin reproduction, this could lead to strongly split sex ratios, promoting the evolution of female helping. Indeed, it has been suggested that risks associated with mating (e.g., exposure to predators or pathogens; Whitcomb et al 1973;Daly 1978;Wing 1988;Helms et al 2016) could select for virginity as an alternative reproductive strategy for haplodiploid females (Godfray and Hardy 1993;Godfray and Cook 1997;Tilquin 2015).…”
mentioning
confidence: 99%